Komitmen Investasi Uni Emirat Arab (UEA) pada Indonesia Investment Authority (INA) 2021 - Ahmad Mudhofarul Baqi (Intermestic: Journal of International Studies, 2022)
This article explains the UAE commitment as the largest major investor in the INA. This commitment contrasts with the realization of UAE's investment in Indonesia, which was only U$ 0.2 million and was in the 50th position in Q1 2021, an also contrary to the Indonesia's economic performance which is experiencing contraction and the decrease of corruption perceptions index. Researcher uses explanative research methods with yield institutions approach from K.S Reddy. This study found that the UAE's commitment to invest in INA is based on influencing and resulting factors. The influencing factors related to the UAE's outward investment strategy through the ADIA, the increasing intensity of bilateral and Indonesian investment diplomacy to the UAE. and the resulting factor in term of potential returns and the UAE's economic integration in the IUAE-CEPA. This indicates that the determination of UAE`S investment drive by economic and political motives.